On the nomenclature of the Pale Blue Flycatcher Cyornis unicolor infuscatus E. Hartert, 1902 (Aves: Muscicapidae) with lectotype designation for Cyornis cyanopolia Blyth, 1870 - Quaisser, Christiane (Zootaxa, 2010)
In autumn 1869, Edward Blyth (1810–1875) visited the bird collection of the Rijks Museum van Natuurlijke Historie in Leiden (RMNH, now: Netherlands Centre for Biodiversity Naturalis, NCB, Leiden) to check its holdings of birds from India, and he then published his findings accompanied by taxonomic notes in the journal Ibis (Blyth 1870: 157–176). One of the taxa mentioned was a muscicapid flycatcher of which he had examined specimens collected on Sumatra, Java and Borneo. The reason Blyth listed them in this publication was that, to his eye, they appeared similar to birds he already knew and had described under the name Cyornis unicolor Blyth, 1843, from Sikkim. However, instead of applying this name in his discussion of these birds in the Leiden collection, presumably because of some uncertainty he retained MS names mentioned on their museum labels, listing them as “Cyornis cyanopolia (Boie)” and “Muscicapa infuscata (Müller)” (Blyth 1870). In doing so he laid the ground for a long-sustained dispute over name availability, redoubled by the discovery of Finsch (1901) that more than one taxon was involved. Aspects of this situation have been summarized recently by Dickinson et al. (2002), Mees (2004) and LeCroy (2008).